Morphology of developing larvae and a dichotomous key for five bubble-nesting Betta species (Teleostei: Osphronemidae) - Poungcharean, Santi; Limpivadhana, Domes (Zootaxa, 2022)
The morphology of larvae of five bubble-nesting Betta species (B. imbellis, B. mahachaiensis, B. siamorientalis, B. smaragdina, and B. splendens) from Thailand was described from specimens reared in the laboratory from wild-caught parents. For all species, the mean notochord length (NL) of the larvae ranged from 2.37 to 2.58 mm. Larvae reached the flexion stage within 9–15 days (NL = 3.22–5.21 mm) and the juvenile stage within 40–45 days (standard length = 10.45–12.18 mm). The main characteristics of hatched larvae for all species were an oblong and slightly compressed body, a small and rounded head, an oval to rounded eye, and a yolk sac without oil droplets. Pre-flexion larvae for all species have an oblique, terminal mouth, and pectoral buds begin to develop after day 1. During the post-flexion larval stage, rays for the caudal, dorsal, anal, ventral, and pectoral fins begin to develop. Juveniles have a fully developed ventral fin with 2–3 dorsal, central, and ventral stripes, and a caudal spot. The minimal and maximal myomere number and fin rays differed between species. For all species, there were 1–2 dorsal spines, 7–9 dorsal rays, 9–12 pectoral rays, 1 ventral spine, 4–5 ventral rays, 2–4 anal spines, 22–28 anal rays, and 10–12 caudal rays. The different larval stages also differed in pigmentation patterns between species. Pigmentation patterns on the head (pre-orbital, sub-orbital, post-orbital, and sub-opercular bars) and longitudinal stripes on the side of the body could be used to distinguish between different larval stages as well as different species.